2017
DOI: 10.1209/0295-5075/118/68002
|View full text |Cite
|
Sign up to set email alerts
|

Ranking influential spreaders is an ill-defined problem

Abstract: Finding influential spreaders of information and disease in networks is an important theoretical problem, and one of considerable recent interest. It has been almost exclusively formulated as a node-ranking problemmethods for identifying influential spreaders rank nodes according to how influential they are. In this work, we show that the ranking approach does not necessarily work: the set of most influential nodes depends on the number of nodes in the set. Therefore, the set of n most important nodes to vacci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…By an elaborately designed model, Gu et al. (2017) showed that there is no ground truth in ranking influential spreaders even with a given dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…By an elaborately designed model, Gu et al. (2017) showed that there is no ground truth in ranking influential spreaders even with a given dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of actually running the spreading process, these metrics are mostly based on the local or global topology of a node in the network, for instance, number of immediate neighbors [28,29,59,157], global position [17,158,159,160,161,162], number of shortest paths [163,164,165,166], random walks [167,168,169], eigenvectors [170,171,172,173], path counting [174,175,176,177], etc. Even though the optimal metric that performs best for all spreading dynamics on all underlying networks does not seem to exist [178,179,180], these centrality-based approaches are still persistently used due to their simplicity and relative satisfactory performance in some occasions.…”
Section: Greedy Algorithmsmentioning
confidence: 99%
“…For vaccination, we will use the average outbreak size from one random seed node to estimate the importance of a node [3,8,15,22]. One could, optionally, rephrase it as a cost problem [12].…”
Section: A Importancementioning
confidence: 99%
“…We will, in general, call these sets active nodes and denote the number of them as n. We will try to find the optimal sets of active nodes (and call them optimal nodes). Note that this is not the same as ranking the nodes in order of importance and take the n most important ones-such a "greedy" approach can in many cases fail [8,14].…”
Section: A Importancementioning
confidence: 99%